2020
DOI: 10.1007/s10479-020-03775-6
|View full text |Cite
|
Sign up to set email alerts
|

Social media and sensemaking patterns in new product development: demystifying the customer sentiment

Abstract: Artificial intelligence by principle is developed to assist but also support decision making processes. In our study, we explore how information retrieved from social media can assist decision-making processes for new product development (NPD). We focus on consumers' emotions that are expressed through social media and analyse the variations of their sentiments in all the stages of NPD. We collect data from Twitter that reveal consumers' appreciation of aspects of the design of a newly launched model of an inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 107 publications
(145 reference statements)
0
26
0
1
Order By: Relevance
“…Social media is increasingly being used by organisations to manage business activities and relationships among supply-chain stakeholders (Choi et al, 2020;Huang et al, 2020;Singh et al, 2018) including, new product development (Giannakis et al, 2020), service improvement (Fan & Niu, 2016), daily sales forecasts (Cui et al, 2019), and information dissemination (Kanagarajoo et al, 2019). The prevalence and speed at which social media platforms (e.g., WeChat, Facebook, LinkedIn, Twitter, Flickr, What-sApp) facilitate the exchange of real-time data (Gorwa & Guilbeault, 2020;Rousidis et al, 2020) has made it a popular tool for effective supply chain management (Choi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social media is increasingly being used by organisations to manage business activities and relationships among supply-chain stakeholders (Choi et al, 2020;Huang et al, 2020;Singh et al, 2018) including, new product development (Giannakis et al, 2020), service improvement (Fan & Niu, 2016), daily sales forecasts (Cui et al, 2019), and information dissemination (Kanagarajoo et al, 2019). The prevalence and speed at which social media platforms (e.g., WeChat, Facebook, LinkedIn, Twitter, Flickr, What-sApp) facilitate the exchange of real-time data (Gorwa & Guilbeault, 2020;Rousidis et al, 2020) has made it a popular tool for effective supply chain management (Choi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore. existing studies have either focused on the 3Vs-volume, velocity, and variety of data and their influence on the NPD (Johnson et al, 2017) or the role played by social media in NPD (Giannakis et al, 2020;Zhan et al, 2018). Rothaermel and Deeds (2006) found that the alliance type and experience act to moderate the relationship between a high-technology venture's R&D alliances and its performance in NPD.…”
Section: Discussionmentioning
confidence: 99%
“…This generated competitive advantage for firms competing in dynamic turbulent environments. NPD in the age of big data has gained significant momentum (see, Johnson et al, 2017;Zhan et al, 2018;Sun & Liu, 2020;Giannakis et al, 2020;Liu et al, 2020;Cappa et al, 2021). Johnson et al (2017) further argue that organizations are increasingly investing in big data analytics capability to transform their NPD activities.…”
Section: Introductionmentioning
confidence: 99%
“…System development is carried out using system design techniques, namely prototyping. This technique aims to model a system for detecting sentiment based on social media emotions [36], [37]. The prototyping process uses three main stages in text processing: preprocessing, emotion detection based on sentiment analysis, and cross-validation testing.…”
Section: Methodsmentioning
confidence: 99%